Prevalence and factors associated with work related musculoskeletal disorders of patient transfer by nurses in health care - Widodo, Silvi Rushanti; Dewi, Ratna Sari; Widyaningrum, Retno (Universitas Sultan Ageng Tirtayasa, 2024)
Musculoskeletal disorders (MSDs), or muscle injuries, are some of the most common health problems worldwide. These disorders can have serious consequences, affecting physical health, mental well-being, time, productivity, and finances, often leading to significant losses. This study aims to identify the prevalence and factors linked to work-related musculoskeletal disorders (WRMSDs) among nurses who perform patient transfers in healthcare settings. A cross-sectional study was carried out from July to August 2023. The study included all nurses working in healthcare facilities during this period who met the inclusion criteria. Eligible participants were licensed nurses with at least one year of experience in the selected hospitals. Nurses who were unwilling to participate or unavailable during the data collection period were excluded. The study aimed to include the entire population of nurses working in the hospital, and the final sample was selected using purposive sampling. During the data collection phase, 40 nurses were available and met the eligibility criteria for participation. The findings revealed that gender is associated with musculoskeletal disorders among nurses [AOR: 2,110, 95% CI (0,165–27,017)]. Age [AOR: 0,000] and body mass index (BMI) [AOR: 0,345, 95% CI (0,077–1,538)] were also significant factors. Nurses over 35 years old and those who were obese had a higher risk of developing musculoskeletal disorders. Work experience more than 20 years was another factor linked to MSDs [AOR: 2,646, 95% CI (0,188-37,233)]. Additionally, education level and marital status were found to be associated with these disorders. In conclusion, a significant proportion of nurses involved in patient transfers experience work-related musculoskeletal disorders, with the lower back and neck being the most commonly affected areas. Key factors contributing to WRMSDs include gender, age, body mass index, work experience, education level, and marital status.